1993
DOI: 10.1073/pnas.90.2.745
|View full text |Cite
|
Sign up to set email alerts
|

Acidic C terminus of vaccinia virus DNA-binding protein interacts with ribonucleotide reductase.

Abstract: Evidence from prokaryotic systems suggests that enzymes of dNTP synthesis are organized near the DNA replication apparatus, allowing direct utilization of dNTPs at their sites of synthesis. To investigate whether similar interactions exist within a eukaryotic environment, we have prepared anti-idiotypic antibodies to the small subunit of vaccinia virus ribonucleotide reductase, and we used these antibodies to search for proteins that interact with this enzyme. This approach identified a 34-kDa viral phosphopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Interestingly, these were the only three mutants that were unable to support virus viability in vivo. Additionally, as stated above, it has been previously proposed that the acidic C-terminal 81 amino acids (aa) of I3 can mediate an interaction with the small subunit of the viral ribonucleotide reductase (RR) (6). The lesions within the I3-5 and -7 alleles fall within this domain, and the subtle changes introduced in these I3 proteins may be sufficient to disrupt the I3-RR interaction and may contribute to their inability to support viral replication in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these were the only three mutants that were unable to support virus viability in vivo. Additionally, as stated above, it has been previously proposed that the acidic C-terminal 81 amino acids (aa) of I3 can mediate an interaction with the small subunit of the viral ribonucleotide reductase (RR) (6). The lesions within the I3-5 and -7 alleles fall within this domain, and the subtle changes introduced in these I3 proteins may be sufficient to disrupt the I3-RR interaction and may contribute to their inability to support viral replication in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Infected and mock-or siRNA-treated cells were harvested at the indicated time points (3,6,8,10,12, and 18 hpi) and subjected to Southern dot blot analysis as previously described (51). DNA was applied to Zeta Probe nitrocellulose (Bio-Rad) and detected using a radiolabeled probe representing the HindIII E and F fragments of the vaccinia virus genome; the bound probe was visualized by autoradiography and quantified on a PhosphorImager Storm Scanner using ImageQuant software.…”
Section: Figmentioning
confidence: 99%
“…It is known that the B1R protein is localized in cytoplasmic virus factories where viral replication occurs (Banham & Smith, 1992), and it is tempting to speculate that the binding of the ribosomal protein $2 kinase to the 36K protein may have the physiological function of directing the enzyme to this location. The viral ssDNA-binding phosphoprotein does appear to have the ability to associate with different proteins, as it was recently shown that it interacts with the vaccinia virus ribonucleotide reductase (Davis & Mathews, 1993). The finding that the ssDNA-binding phosphoprotein is most probably a substrate for the ribosomal protein S2/Sa kinase is interesting for another reason.…”
Section: Discussionmentioning
confidence: 89%
“…This phosphoprotein binds ssDNA cellulose and is eluted with 0.25 M-NaC1. Recently, it has been reported that it is encoded by the gene I3 of vaccinia virus (Davis & Mathews, 1993; S.C. Rochester & P. Traktman, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…At about the same time as we were making these observations, our laboratory discovered an SSB protein encoded by vaccinia virus, which interacts specifically with the virus‐coded ribonucleotide reductase (RNR) through its acidic C‐terminus (Davis and Mathews, 1993; I. Rajagopal, unpubl. data).…”
Section: Introductionmentioning
confidence: 99%